Associations between diet quality and depression, anxiety, and fatigue in multiple sclerosis - Saul, A.; Taylor, B.V.; Blizzard, L.; Simpson-Yap, S.; Oddy, W.H.; Probst, Y.C.; Black, Lucinda; Ponsonby, A.L.; Broadley, S.A.; Lechner-Scott, J.; van der Mei, I. (ELSEVIER SCI LTD, 2022)
Background: Many people with multiple sclerosis (MS) modify their dietary intake post diagnosis, but there is little evidence that dietary modifications influence MS outcomes. Methods: People with a first clinical diagnosis of central nervous system demyelination were followed annually for 10 years. Depression, anxiety, and fatigue were assessed at the 5-and 10-year reviews using the Hospital Anxiety and Depression Scale and Fatigue Severity Scale, respectively. Dietary intake in the preceding 12 months was assessed at baseline, and 5-and 10-year reviews using a food frequency questionnaire. We used the Australian Recommended Food Score (ARFS) and the Diet Quality Tracker (DQT) to assess diet quality. Results: A higher diet quality in the previous 12 months using the ARFS score, but not the DQT, was associated with lower levels of depression (e.g., highest vs lowest quartile: β=-1.35,95%CI=-2.44,-0.26,p=0.01), but neither score was associated with anxiety or fatigue. After assessing diet quality prospectively with outcomes five years later, we found that higher ARFS score, but not DQT score, was associated with lower levels of subsequent anxiety and depression (highest vs lowest quartile; Anxiety: β=-1.61,95%CI=-2.76,-0.46,p=0.01, Depression: β=-1.25,95%CI=-2.44,-0.07,p=0.04), but not fatigue. No associations were observed between diet quality and subsequent change in depression and anxiety over five years, although an association was observed between diet quality and change in fatigue (e.g., highest vs lowest DQT quartile: β=-1.06,95%CI=-1.92,-0.21,p=0.02). When examining the cumulative effect of diet quality across the study period with our 10-year outcomes, only the cumulative DQT score was associated with depression but not anxiety or fatigue. Conclusion: We found significant inverse associations between diet quality and depression and anxiety, but the effect sizes were modest and there was a lack of consistency between the two diet quality measures (ARFS and DQT). A diet measure that correlates with diet quality might underlie our observed associations.